On The Verification and Realization of VANET Applications - Ahmed, Hazem; Pierre, Samuel; Quintero, Alejandro (International Journal of Sensors Wireless Communications and Control, 2016)
Modeling and realization of Vehicular Ad-Hoc Network (VANET) applications and protocols are very challenging; due to VANET`s unique mobility, driver behavior, signaling and road topology requirements. Although network simulators are commonly used to evaluate wireless network per-formance, VANET applications require mobility simulators to mimic road traffic topology and mobility. However, network and mobility simulators fall short of evaluating Quality of Experience (QoE) and Quality of Service (QoS) of context-rich applications with multiple user interactions. Using real hardware provides a solid mechanism to evaluate QoE and QoS in real time, though it is very expensive to use in large networks and difficult to reproduce specific VANET scenarios such as collisions and signaling changes due to speed and road topology. Emulation techniques combine the benefits of using both simulation and hardware approaches. Recently, multiple Ad-Hoc emulators have been developed, but they are not tailored to VANET`s requirements. In this article, the most suitable network and mobility simulators and their integrations for VANET are surveyed. Subsequently, their features, popularity and challenges are compared, the best ones corresponding to VANET application conditions are rec-ommended. Moreover, a comprehensive review is performed on Ad-Hoc emulators showing the benefits and suitability of each one for VANET applications. This article serves as a starting point for the development of comprehensive VANET emulators and testbeds; it also acts as a start-up guide for researchers to select the best tools for VANET application, protocol modeling, simulation, and emulation.
Keywords: Vehicular Ad-Hoc Networks (VANET)